Optimizing Price of Credit Default Swaps for Dynamic Project System of Public-Private Partnership - Ming Wu; Wenya Lv; Qiuji Sun (Discrete Dynamics in Nature and Society)
Most project operations management belongs to the type of public-private partnership (PPP), which is usually dynamic. This paper aims to propose a method for optimizing the price of credit default swaps (CDS) for the dynamic PPP system. This study investigates the credit risk measurement of PPP project financing and the pricing of risk mitigation instruments which are widely used in the case of immature markets in the early stage of China’s PPP development. Based on the credit risk measurement theory of the corporate and debt ratings, this paper considers the differences in various credit enhancement methods in the equity-like debt agreement and determines the credit rating of the equity-like debt in PPP projects. Some optimization methods are also proposed to derive the probability of default, so as to determine the price of the credit risk mitigation instrument of CDS which is based on the equity-like debt.